Potential Prognostic Impact of Dopamine Receptor D1 (rs4532) Polymorphism in Post-stroke Outcome in the Elderly - Park, Hae-Yeon; Kim, Youngkook; Oh, Hyun Mi; Kim, Tae-Woo; Park, Geun-Young; Im, Sun (Frontiers in Neurology, 2021)
Background: Single-nucleotide polymorphisms (SNPs) may affect post-stroke motor recovery, and some SNPs have been implicated in swallowing disturbances after stroke. Certain SNPs may also have altered influences according to different age. Objective: This post-hoc study investigated whether SNPs have different effects on dysphagia recovery between the elderly vs. young stroke patients. Methods: Analysis was conducted from a previous study including 218 stroke subjects with dysphagia. They were stratified into two groups, aged <65 and aged ≥65 years. The primary outcome was persistence of nil per mouth (NPM) at 3 months post-stroke onset. Association between outcome and nine different SNPs were investigated. Results: The elderly group (50%, n = 103) showed poorer swallowing outcomes than the young group. The minor allele of the dopamine receptor D1 (DRD1, rs4532) polymorphism showed potential association (p = 0.022) with an increased risk of NPM at 12 weeks post-stroke in the elderly, both in the additive (OR, 2.94; 95% CI, 1.17–7.37) and dominant models (OR, 2.93; 95% CI, 1.04–8.23) but did not reach statistical significance after Bonferonni correction. Logistic regression analysis showed that in those aged ≥65 years, models including the minor allele of rs4532 predicted the risk of the poor outcome with good accuracies even after adjustment of clinical factors, such as previous pneumonia episodes (AUROC, 0.86; 95% CI, 0.79–0.93) or the National Institutes of Health Stroke Scale (AUROC, 0.82; 95% CI, 0.67–0.92). In contrast, those aged <65 years seemed not to be affected by the presence of the rs4532 polymorphism, and models that included intubation history (AUROC, 0.81; 95% CI, 0.73–0.90) or previous pneumonia episodes (AUROC, 0.77; 95% CI, 0.68–0.87) showed modest levels of accuracies in predicting NPM at 12 weeks poststroke. Conclusions: Our study suggests a possible association between the rs4532 and post-stroke swallowing recovery, primarily in those aged ≥65 years. Certain SNPs may lead to less favorable outcomes in the elderly. The gene–age interaction should be considered in post-stroke swallowing recovery. Clinical Trial Registration:https://www.clinicaltrials.gov, Unique identifier [NCT03577444].